Control of diesel-electric AC/DC traction drive of motor truck WŽB 10.1-M - Mašek, Zdeněk; Novák, Jaroslav; Sadílek, Ondřej; Lelek, Tomáš (My University, 2017)
The paper describes the control of traction drive and control systems properties of special rail vehicle WŽB10.1-M used in Prague metro (subway). Measured values of main quantities of control system and experience from duty are included. Software for traction drive control system was developed at University of Pardubice.
Řízení diesel-elektrického AC/DC pohonu kolejového vozidla WŽB 10.1-M
Keywords: rail; vehicle; metro; subway; traction; drive; diesel; engine; control; system; tractive; effort; WŽB; MUV; MMD; motorový; vozík; metro; trakční; pohon; diesel; motor; řídící; systém; tažná; síla; WŽB; MUV; MMD